ANALISIS PERILAKU KONSUMEN DALAM MENGGUNAKAN MOBILE BANKING BCA DI KOTA SURABAYA - Lovitasari, Sherline (Seminar Nasional Ilmu Terapan, 2024)
The rapid development of science and technology in the era of globalization has brought many new innovations in various fields, including banking. This research aims to determine consumer behavior towards using BCA mobile banking in the city of Surabaya. The research method used is descriptive qualitative. The data collection technique used was through interviews, observation and documentation with 10 selected sources who met the criteria determined by the researcher. The results of interviews with 10 informants revealed that BCA mobile banking is widely used by the public, BCA ATMs are everywhere, QRIS payments can be used at any merchant, the features and appearance are simple.